Crusade the untold story of the Persian Gulf War - Atkinson, Rick (Houghton Mifflin, 1993)
Integrating interviews with individuals ranging from senior policymakers to frontline soldiers, a look at the Persian Gulf War shows how the conflict transformed modern warfare.